The Influence of Financial Literacy, Financial Technology, and Inclusion Finance on MSME Financial Performance in Cilegon City - Hasanudin, Agus Ismaya; Rahmiyanti, Sev (inovator, 2023)
MSME growth needs to be increased through knowledge and experience to increase national economic growth. White a variety of knowledge and experience, will create innovations in literacy, technology, and financial inclusion to facilitate public access to financial services. This study aims to determine the effect of financial literacy, financial technology (FinTech), and financial inclusion on the financial performance of MSMEs in Cilegon City. The data collection technique used 100 respondents who were randomly selected from Cilegon City MSME entrepreneurs. In conducting research using multiple regression hypothesis testing using SPSS software. In this study, all variables have a significant effect.